2020
DOI: 10.14814/phy2.14337
|View full text |Cite
|
Sign up to set email alerts
|

Calcium‐sensing receptor regulates intestinal dipeptide absorption via Ca 2+ signaling and IK Ca activation

Abstract: Although absorption of di-and tripeptides into intestinal epithelial cells occurs via the peptide transporter 1 (PEPT1, also called solute carrier family 15 member 1 (SLC15A1)), the detailed regulatory mechanisms are not fully understood. We examined: (a) whether dipeptide absorption in villous enterocytes is associated

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…We have previously reported Ca 2+ signaling regulation of ion secretion and absorption through SGLT1 in the intestinal epithelium ( Zhang F. et al, 2019 ; Yinghui et al, 2021 , Zhang et al, 2021 ). We also revealed that Ca 2+ signaling regulates H + /peptide transporter PEPT1 to mediate intestinal Gly-Sar uptake in mice ( Xu et al, 2020 ). However, it is currently unknown if Ca 2+ signaling regulates intestinal Gln uptake.…”
Section: Introductionmentioning
confidence: 88%
“…We have previously reported Ca 2+ signaling regulation of ion secretion and absorption through SGLT1 in the intestinal epithelium ( Zhang F. et al, 2019 ; Yinghui et al, 2021 , Zhang et al, 2021 ). We also revealed that Ca 2+ signaling regulates H + /peptide transporter PEPT1 to mediate intestinal Gly-Sar uptake in mice ( Xu et al, 2020 ). However, it is currently unknown if Ca 2+ signaling regulates intestinal Gln uptake.…”
Section: Introductionmentioning
confidence: 88%
“…The absorbed Gly-Sar stimulates basolateral CaSR, leading to the activation of phospholipase C (PLC) and the increase of [Ca 2+ ] i , which then activates IK Ca to provide the driving force for PEPT1 transepithelial uptake. 60 In the study of lipids absorption, early research studied that luminal Ca 2+ increases the absorption of LCFA in rat jejunum; there is a potential for that Ca 2+ transport and LCFA transport to be correlated in the brush border and the basolateral membrane of IEC. 61 Calcium channel blockers (CCBs) affect plasma lipid level and lipoprotein me- Hiroshi Arakawa et al found that the nutrient absorption and energy supply network composed of the Cav1.3-Ca 2+ -PKCβII mechanism mainly coordinated glucose absorption and PEPT1-mediated peptide absorption.…”
Section: The Ca 2+ -Channels In the Intestinal Nutrient Uptakementioning
confidence: 99%
“…Jingyu Xu et al found that [Ca 2+ ] i stimulates the positive feedback pathway of peptide absorption. The absorbed Gly‐Sar stimulates basolateral CaSR, leading to the activation of phospholipase C (PLC) and the increase of [Ca 2+ ] i , which then activates IK Ca to provide the driving force for PEPT1 transepithelial uptake 60 …”
Section: Intestinal Channels Mediate Nutrient Transportmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned before, peptide transport over the plasma membrane occurs in cotransport with protons, leading to cytosolic acidification of enterocytes, a process that can be visualized by live-cell imaging using fluorescent probes [ 10 , 74 ] ( Figure 4 ). Also, many transporter activities (e.g., PEPT1) [ 163 ], intracellular translocation events (e.g., GLUT2) [ 164 ] and receptor activation involve intracellular calcium signalling that can be visualized in the same way using the calcium-indicator Fura-2-AM. Hence, intracellular changes immediately reflect transport activities, providing direct evidence for substrate fluxes or for activation of receptors by a putative ligand/drug.…”
Section: Human Intestinal Organoids and How They Can Improve Drug Screeningmentioning
confidence: 99%